Formation and development of the language training methodology for foreign students at classical university. Part 4. Language training of foreign medical students in the english medium education format - Ushakova, N.; Kushnir, I.; Trostynska, O.; Aleksieienko, T. (Викладання мов у вищих навчальних закладах освіти на сучасному етапі: Міжпредметні зв'язки, 2024)
This article continues a series of scientific research focusing on the stages of formation and development of the methodology of language training of foreign higher education students. Specifically, it examines the work of the Language Training Department at the Institute of International Education for Study and Research of V.N. Karazin Kharkiv National University. The objective of the article is to elucidate the system of teaching Ukrainian to foreign medical students pursuing higher education in English and its practical implementation. The article analyses theoretical research and methodological developments carried out by the department’s teachers in the field of language training of foreign medical students. The theoretical framework encompasses various educational paradigms relevant to the training of higher medical education students, the systematization of training principles, including professional dialogue, and the characterization of levels and elements within the integrative system of professional and communicative training of the target group. Furthermore, the article scrutinizes the normative, procedural, and evaluative functions of linguistic discipline curricula. It examines the principles governing the selection of content elements and topics that embody the linguistic, speech, and professional components required for teaching the Ukrainian language to future doctors. Theoretical developments have led to the characterization of principles guiding the creation of textbooks aimed at forming the communicative competence components of future medical professionals. An analysis of a series of textbooks demonstrates their effectiveness in fulfilling the objectives outlined in the work programs and in fostering general and professional competences among higher medical education students. In response to contemporary challenges, such as the need to adapt to educational disruptions caused by pandemics and martial law, the authors underscore the importance of integrating modern digital technologies into the educational process. The article explores the possibilities of digital storytelling technology and evaluates the alignment of distance courses, created by departmental teachers on the Moodle platform, with the objectives of language training. Looking ahead, the authors envision optimizing the formation of medical students’ communicative competence through theoretical development and the implementation of a comprehensive model in the educational process. This model would blend effective traditional teaching strategies with the capabilities of modern digital technologies and platforms.